Understanding the Effect of Surface Terrain on Pollution Transport around Gebeng Industrial Area - Norliyana, Erain; Law, Woon Phui; Noram Irwan, Ramli; Siew, Choo Chin; Jolius, Gimbun (Informatics Publishing Limited, 2017)
Objectives: Air pollution dispersion is greatly affected by the wind speed and direction. Most often the pollution dispersion from industrial area is not fully understood. In the present work, the effect of surface topology on the wind speed and atmospheric turbulent around the Gebeng industrial area in Pahang was studied using a Computational Fluid Dynamics (CFD) method. Methods/Statistical Analysis: The typical southeastern wind with a speed of about 1.3003 m/s corresponding to the actual speed of approximately 5 km/h was considered for validation. The turbulent flow was modelled using k-ε model. The model was compared with the Laser Doppler Velocimetry (LDV) measurement onthe scale-down rig. Findings: The CFD prediction showed good agreement within 10% deviation with the experimental measurement via LDV. It was found that the plume of noxious gas driven by the eastern wind can affect the nearby residential area R2, whereas the western wind is affecting the residential area R1. In the presence of hill obstacle, the gas plume moves southward into the flat terrain. Application/Improvements: Results from this work may be useful to understand the risk of air pollutant dispersion round Gebeng industrial area.